Picture say all ik its easy but im stuck somehow:/
Follow Math Help Forum on Facebook and Google+
You can solve it with co factor expansion since we know that the determinant is going to be zero. We then have (1)*(x-x)-(x-1)(x^2-4)+(-1)(x^2-4) = 0 <=> x_1 = -2, x_2 = 0, x_3 = 2
Thats not how i shall solve it.. Factor is like next chapter they somehow solve this equation with that det
Can you specify how you are supposed to solve calculate the determinant?
Its the (2) the prob i get same but dont get -x^3
Originally Posted by Petrus Its the (2) the prob i get same but dont get -x^3 Do you mean were x+4(x-1)-x^2+4-x-x^2(x-1) = x+4x-4-x^2+4-x-x^3+x^2 = 4x-x^3 ?
Just u type it made me solve it idk why but now i understand it!!! Ty alot
View Tag Cloud